Defoliation effects of Diorhabda carinulata on tamarisk evapotranspiration and groundwater levels. Issue 8 (6th February 2015) - Sueki, Sachiko; Acharya, Kumud; Huntington, Justin; Liebert, Ryan; Healey, John; Jasoni, Richard; Young, Michael
Abstract: Diorhabda carinulata (northern tamarisk beetle) has been released in the western United States as a biological control agent for the invasive plant Tamarix spp. (tamarisk). A few studies have been conducted analysing the effects of beetle defoliation on tamarisk water consumption, but predefoliation and post‐defoliation comparison based on field data is scarce. The question of whether beetles substantially alter tamarisk water consumption is still open for discussion. In this study, an eddy covariance station and groundwater monitoring well were installed in a tamarisk stand along the Virgin River near Mesquite, NV, in 2010 to observe the impacts of tamarisk defoliation on evapotranspiration (ET) and groundwater levels. ET was calculated using the eddy covariance method and the White method and supported by Landsat remote sensing estimates. Data collected in 2010 established a baseline since the beetles arrived at the site in late 2010 and started feeding on foliage causing tamarisk trees to turn to brown during 2011. Repeated defoliations in 2011 and 2012 show that post‐defoliation ET values and magnitude of diurnal groundwater‐level fluctuations decreased compared with the predefoliation values. Estimated annual ET and annual average daily groundwater fluctuations were reduced by 18% and 35%, respectively. However, the magnitude of effects of defoliation was dependent on the growth stage of tamarisk at the time of defoliation. Also, ET recovered within a month as tamarisk established new leaves. Results from this study suggest that long‐term changes in ET are highly dependent on repeated defoliation occurrences over several years. Copyright © 2015 John Wiley & Sons, Ltd.